Antibiotics Resistance in Poultry and its Solution - Samad, Abdul (Green Publisher Indonesia, 2022)
The poultry sector has grown quickly over the past three decades. This has led to increased use of antibiotics as both medicinal and growth-promoting drugs. Concerns about the emergence of antibiotic resistance in bacterial populations, the presence of antibiotic residues in poultry products, and the increasing consumer demand for products free of antibiotic residues have accelerated the search for alternatives that could replace antibiotics without causing a loss in productivity or product quality. These alternatives to antibiotics in chicken include the use of organic acids, probiotic microorganisms, prebiotic substrates that encourage the establishment of beneficial bacterial populations, or symbiotic (combinations of prebiotics and probiotics), which boost production and maintain bird health. Phytobiotics, antimicrobial peptides, herbal medications, vitamins and minerals, and plant extracts are more examples. Probiotic organisms compete with pathogenic organisms for colonization sites in the gastrointestinal tract, redirect fewer nutrients to harmful microorganisms and the toxins they produce, and stimulate the immune system. Prebiotics also present an option since they change the immune system and intestinal microorganisms to prevent pathogens from colonizing the gut and to promote the growth of healthy microflora. However, further research is required to select probiotic, prebiotic, or synbiotics either alone or in combination that can result in the selection of strains capable of functioning well in the gastrointestinal system. Using synbiotics is still a preferable method for improving poultry production. Researchers can utilize the information in this review to further their understanding of antibiotic alternatives for poultry birds without sacrificing the welfare or performance of the birds.